Field application of an improved protocol for environmental DNA extraction, purification, and measurement using Sterivex filter - Wong, Marty Kwok-Shing (Sci Rep, 2020)
Environmental DNA (eDNA) is increasingly popular as a useful non-invasive method to monitor and study biodiversity and community structure in freshwater and marine environments. To effectively extract eDNA from the filter surface is a fundamental factor determining the representativeness of the samples. We improved the eDNA extraction efficiency of an established Sterivex method by 12- to 16-fold using a larger volume of lysis buffer mix coupled with backflushing the cartridges. The DNeasy extraction column could be overloaded when the environmental sample input is high, possibly due to a higher nonspecific binding present in environmental samples, thus resulting in a relatively lower quantity measured. Therefore, we included an internal control DNA in the extraction to monitor the extraction and purification efficiencies in field samples, which is crucial for quantification of original eDNA concentration. The use of Takara Probe qPCR Mix supplemented with protein-based additives improved the robustness of the real time PCR assay on inhibitor-rich environmental samples, but prior purification by Qiagen PowerClean Pro Cleanup kit could be essential for inhibitor-rich water samples, even though the recovery rate was unexpectedly low (average 33.0%). The improved extraction and quantification complement the qualitative analyses including metabarcoding and metagenomics in field application.